Penerapan Model Reciprocal Teaching untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SD Negeri 016 Rambah Samo - Indriyani, Ceci; Hasibuan, Abdul Putra Ginda; Marta, Eni; Elvina, Elvina (Indo-MathEdu Intellectuals Journal, 2024)
This research is classroom action research (PTK) which aims to improve student learning outcomes through the application of the reciprocal teaching model in mathematics learning. Data collection techniques are carried out in the form of student activity observation sheets, teacher activity observation sheets and test questions. The results of this research show that in cycle I and cycle II there was an increase. The learning outcomes in cycle I, meeting I, had an average score obtained by students, namely 54.12, then in cycle I, meeting II, the average score obtained by students was 65.88. Then in cycle II, at meeting I, the average score obtained by students was 71.18, and at meeting II, the average score for students was 85.88. Besides increasing student learning outcomes, student observation sheets also increased. In cycle I, meeting I, student observations were 50%, then in cycle I, meeting II, it increased to 60%. In cycle II, meeting I, the student's ability still increased to 80%, and in cycle II, meeting II, it increased to 90%. Based on the results of the research that has been carried out, it can be concluded that the application of the reciprocal teaching model can improve student mathematics learning outcomes for class V students at SD Negeri 016 Rambah Samo